Metastatic Bladder Cancer Presenting with Persistent Hematuria in Young Man with Cystic Fibrosis - Premal Patel; Harvey R. Rabin; Michael M. Vickers; Michael D. Parkins (Case Reports in Pulmonology)
We report a case of metastatic bladder cancer developing in a young man with cystic fibrosis (CF) that was initially diagnosed as ureterolithiasis and managed as renal colic. With the improved survival of patients with CF, an increasing burden of extrapulmonary disease manifestations is apparent. Renal colic is observed at an increased frequency in patients with CF relative to the general population and is a commonly recognized cause of hematuria. However, CF patients harboring a malignancy are recognized to be at increased risk of delayed identification owing to atypical symptoms and lack of demographic risk factors. This case illustrates how investigations to rule out malignancy are warranted in those CF patients not responding to therapies directed towards presumptive diagnoses.